2020
DOI: 10.1002/app.48972
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion during film formation of ionically cross‐linked acrylics investigated with Förster resonance energy transfer (FRET)

Abstract: Polymer interdiffusion is crucial to obtain continuous films from aqueous polymer dispersions. Here, interdiffusion in films from dispersions of acrylates which were ionically cross-linked prior to film formation was studied by Förster resonance energy transfer analysis. Dispersions of copolymers of n-butyl acrylate, methacrylic acid, and zinc dimethacrylate (ZnDMA) were investigated. ZnDMA was used as a co-monomer to ionically cross link the polymers during the synthesis. Ionic cross-linking does not prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…5. The nanospheres have to balance two forces, i.e., adhesion between polystyrene nanospheres and adhesion between polystyrene nanospheres and substrate, as they experience polymer interdiffusion, which is the primary cause of defect formation [31].…”
Section: Resultsmentioning
confidence: 99%
“…5. The nanospheres have to balance two forces, i.e., adhesion between polystyrene nanospheres and adhesion between polystyrene nanospheres and substrate, as they experience polymer interdiffusion, which is the primary cause of defect formation [31].…”
Section: Resultsmentioning
confidence: 99%
“…These results illustrate the immense power of using FRET‐based measurements in conjunction with other characterization methods to deconvolute complex physical processes in polymer systems. Furthermore, FRET was employed to investigate interdiffusion of particles within films made from dispersions of acrylates with ionic crosslinks formed by adding zinc dimethacrylate as a comonomer [226] . The FRET dyes were incorporated in the same way as previously mentioned in linear and cross‐linked chains and the results showed that even at high levels of crosslinking, interdiffusion was still possible during film formation and increasing the humidity accelerated the interdiffusion in the ionically cross‐linked films.…”
Section: Polymer Chain Diffusionmentioning
confidence: 99%
“…To overcome the issue of limited mechanical performance, a number of alternatives have been proposed including the use of inorganic/polymer hybrids, [7][8][9][10] chemical [11][12][13][14] and physical [15][16][17][18][19] crosslinking of the polymer after film formation, and the use of multiphase latexes. [20][21][22][23][24] Multiphase systems contain a high T g polymer to improve mechanical performance and a low T g polymer to aid in film formation.…”
Section: Introductionmentioning
confidence: 99%